Lactobacillus plantarum TWK10 Attenuates Aging-Associated Muscle Weakness, Bone Loss, and Cognitive Impairment by Modulating the Gut Microbiome in Mice - Lee, Chia-Chia; Liao, Yi-Chu; Lee, Mon-Chien; Lin, Kun-Ju; Hsu, Han-Yin; Chiou, Shiou-Yun; Young, San-Land; Lin, Jin-Seng; Huang, Chi-Chang; Watanabe, Koichi (Frontiers in Nutrition, 2021)
In humans, aging is characterized by the progressive decline in biological, physiological, and psychological function, and is a major risk factor in the development of chronic disease. Therefore, the development of strategies aimed at attenuating aging-related disorders and promoting healthy aging is critical. In a previous study, we have demonstrated that Lactobacillus plantarum TWK10 (TWK10), a probiotic strain isolated from Taiwanese pickled cabbage, improved muscle strength, exercise endurance, and overall body composition in healthy humans. In this study, the effect of TWK10 on the progression of age-related impairments was investigated in mice. We found that TWK10 not only enhanced muscle strength in young mice, but also prevented the aging-related loss of muscle strength in aged mice, which was accompanied by elevated muscle glycogen levels. Furthermore, TWK10 attenuated the aging-associated decline in learning and memory abilities, as well as bone mass. Further analyses of gut microbiota using next-generation sequencing (NGS) of the 16S rRNA gene showed that the pattern of gut microbial composition was clearly altered following eight weeks of TWK10 administration. TWK10-treated mice also experienced an increase in short-chain fatty acid (SCFA)-producing bacteria and higher overall levels of gut SCFA. Furthermore, TWK10 administration to some extent reversed the aging-associated accumulation of pathogenic bacterial taxa. In conclusion, TWK10 could be viewed as a potential therapeutic agent that attenuates aging-related disorders and provides health benefits by modulating the imbalance of gut microbiota.